Pioglitazone attenuates atrial remodeling and vulnerability to atrial fibrillation in alloxan‐induced diabetic rabbits. Issue 5 (14th September 2017) - Liu, Changle; Liu, Ruimeng; Fu, Huaying; Li, Jian; Wang, Xinghua; Cheng, Lijun; Korantzopoulos, Panagiotis; Tse, Gary; Li, Guangping; Liu, Tong
Summary: Background/Aims: Recent evidence indicates that peroxisome proliferator‐activated receptor (PPAR)‐γ activators exert anti‐inflammatory and antioxidant actions. However, the underlying mechanisms by which these agents prevent atrial remodeling in diabetes are not completely elucidated. We sought to investigate the potential effects of pioglitazone, a PPAR‐γ activator, on atrial remodeling and atrial fibrillation (AF) inducibility in diabetic rabbits. Methods: Alloxan‐induced diabetic rabbits were randomly divided into three groups: diabetes only, diabetes treated with low‐dose pioglitazone (4 mg/day/kg), or diabetes treated with high‐dose pioglitazone (8 mg/day/kg) (n=24 for each group). A total of 24 healthy rabbits served as controls. Eight weeks later, hemodynamic, echocardiographic, and electrophysiological parameters were recorded. Left atrial whole‐cell patch‐clamp studies, histological examination, and Western blot analysis were also performed. Results: In the DM group (6/8 vs 1/8, P <.05), higher AF inducibility, increased amount of fibrosis, lower IN a, and higher IC aL were observed in the DM group compared to controls. Western blot analysis showed that DM increased the expression of extracellular signal‐regulated kinase 2 (ERK2), phosphorylation ERK, transforming growth factor beta‐1, Toll‐like receptor 4, nuclear factor‐κB p50, and heat‐shock protein 70. All of these electrophysiological, histological, ion current density, and protein expression changes were all reduced by pioglitazone. Conclusion: Pioglitazone attenuates diabetes‐induced structural and electrophysiological remodeling in the atria, thereby reducing the vulnerability to AF.